Asymmetric inflation target credibility - Winnie Coleman; Dieter Nautz (Freie Universität Berlin, School of Business & Economics, 2025)
This paper investigates the determinants of inflation target credibility (ITC) using a unique survey we designed to measure the credibility of the ECB's inflation target. Containing over 200,000 responses from German consumers collected between January 2019 and November 2024, our dataset enables us to estimate the effect of both positive and negative deviations of inflation from the 2% target on ITC. In contrast to the symmetry of the ECB's inflation target, we find that ITC is asymmetric, i.e. consumers respond significantly and plausibly signed to target deviations only when inflation is above target. When inflation is below target, however, the credibility of the inflation target cannot be improved by raising the inflation rate to close the gap.
urn:nbn:de:kobv:188-refubium-46130-3
Keywords: D84; E31; E52; E58; 330; Credibility of Inflation Targets; Consumer Inflation Expectations; Expectation Formation